2005
DOI: 10.1128/iai.73.2.730-740.2005
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the ATP-Dependent Protease ClpCP to the Autolysis and Virulence of Streptococcus pneumoniae

Abstract: The ATP-dependent caseinolytic proteases (Clp) are fundamental for stress tolerance and virulence in many pathogenic bacteria. The role of ClpC in the autolysis and virulence of Streptococcus pneumoniae is controversial. In this study, we tested the role of ClpC in a number of S. pneumoniae strains and found that the contribution of ClpC to autolysis is strain dependent. ClpC is required for the release of autolysin A and pneumolysin in serotype 2 S. pneumoniae strain D39. In vivo, ClpC is required for the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…In addition, D39 clpP mutants were unable to colonize the nasopharynx (which S. pneumoniae colonizes in humans) of mice (Kwon et al, 2004). In contrast, despite the clues of the STM screens, clpC and clpL mutations did not affect virulence in intranasal infections (Kwon et al, 2003;Ibrahim et al, 2005). However, fewer clpC mutant bacteria were found in the lungs and blood during early infection (Ibrahim et al, 2005), suggesting perhaps a small role for clpC in establishing systemic S. pneumoniae infection.…”
Section: Streptococcus Pneumoniaementioning
confidence: 95%
See 1 more Smart Citation
“…In addition, D39 clpP mutants were unable to colonize the nasopharynx (which S. pneumoniae colonizes in humans) of mice (Kwon et al, 2004). In contrast, despite the clues of the STM screens, clpC and clpL mutations did not affect virulence in intranasal infections (Kwon et al, 2003;Ibrahim et al, 2005). However, fewer clpC mutant bacteria were found in the lungs and blood during early infection (Ibrahim et al, 2005), suggesting perhaps a small role for clpC in establishing systemic S. pneumoniae infection.…”
Section: Streptococcus Pneumoniaementioning
confidence: 95%
“…To test this hypothesis, clpP null mutants were made in two different S. pneumoniae strain backgrounds. An S. pneumoniae D39 clpP mutant was completely avirulent, while an S. pneumoniae strain TIGR4 clpP mutant strain was less attenuated in a mouse model of infection (Ibrahim et al, 2005). In addition, D39 clpP mutants were unable to colonize the nasopharynx (which S. pneumoniae colonizes in humans) of mice (Kwon et al, 2004).…”
Section: Streptococcus Pneumoniaementioning
confidence: 99%
“…The genes encoding the ClpP peptidase and the Clp ATPase partners are by far the best-studied streptococcal stress genes in terms of virulence potential. The virulence of S. pneumoniae ⌬clpP strains was attenuated in mice, regardless of the administration method (477)(478)(479). The core genome of S. pneumoniae encodes four Clp ATPases (ClpC, ClpE, ClpL, and ClpX), although ClpL does not have the recognition tripeptide responsible for the interaction with ClpP; thus, it functions mainly as a chaperone.…”
Section: General Stress Responses and Virulencementioning
confidence: 99%
“…Transcriptomic and proteomic analyses indicated that ClpE affects pneumococcal pathogenesis by modulating the expression of important virulence determinants and metabolism-related factors (480). Despite participating in several important physiological processes (481,482), ClpC is apparently not required for pneumococcal virulence (477,479), while inactivation of clpX is lethal (303). Although ClpL is required for growth at 43°C and for penicillin tolerance (478,483), an S. pneumoniae ⌬clpL mutant showed a level of virulence similar to that of the parental strain in a murine intraperitoneal infection model (478).…”
Section: General Stress Responses and Virulencementioning
confidence: 99%
“…These transcripts also included genes encoding the reactive oxygen-reducing enzymes superoxide dismutase SodA (ranked 114th), 36 peroxiredoxin reductase AhpC and AhpF (ranked 115th and 147th), 37 and NADH oxidase NOX (ranked 129th), 38 molecular scavengers such as the antioxidant Dpr protein (ranked 76th), 39 clpC (ranked 158th) encoding heat shock protease ClpC involved in tolerance to environmental stress, 40 recA (ranked 169th) encoding the RecA regulator of bacterial SOS responses, and sortase SrtA (ranked 131st) involved in the maturation of extracellular GAS proteins. Molecular chaperones as well as DNA and protein repair functions (chaperone proteases) also were elevated in soft tissues (Supplementary Table 3, see http://ajp.amjpathol.org).…”
Section: Gas Protective Response Augmented In the Soft Tissue Environmentioning
confidence: 99%